2019
DOI: 10.1177/0194599819844755
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Validated Quality of Life and Swallow Outcomes after Transoral Robotic Surgery

Abstract: Objective To systematically review the available evidence on the effects of transoral robotic surgery (TORS) on the posttreatment quality of life (QOL) and swallow function of patients with head and neck cancer. Data Sources PubMed and Ovid electronic databases were searched from inception to July 6, 2016. Specific database functions were applied to maximize the search. Review Methods Articles in the database were reviewed for inclusion by 2 independent reviewers according to predetermined eligibility criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 46 publications
0
15
0
4
Order By: Relevance
“…The most common presentations for HPV+OPSCC are the clinical N2a/N2b stages (AJCC 7th), which together represent 30% to 51% of all patients with HPV+OPSCC 21,44‐46 . Sparing patients definitive and adjuvant radiation and chemotherapy‐related sequelae and side effects would have potential swallowing, salivary, taste, dental, psychosocial, otologic, neurologic, nephrological, hematologic, and financial benefits in the first few years after treatment 23,25‐28,47 . Avoidance of radiation could also eliminate the radiation‐related toxicities that can occur many years later, such as delayed swallowing dysfunction, neck and throat fibrosis, dental decay, osteoradionecrosis of the mandible, hypothyroidism, and radiation‐induced cancers, all of which are less often reported in studies 7,48‐51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common presentations for HPV+OPSCC are the clinical N2a/N2b stages (AJCC 7th), which together represent 30% to 51% of all patients with HPV+OPSCC 21,44‐46 . Sparing patients definitive and adjuvant radiation and chemotherapy‐related sequelae and side effects would have potential swallowing, salivary, taste, dental, psychosocial, otologic, neurologic, nephrological, hematologic, and financial benefits in the first few years after treatment 23,25‐28,47 . Avoidance of radiation could also eliminate the radiation‐related toxicities that can occur many years later, such as delayed swallowing dysfunction, neck and throat fibrosis, dental decay, osteoradionecrosis of the mandible, hypothyroidism, and radiation‐induced cancers, all of which are less often reported in studies 7,48‐51 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that primary surgical treatment with guideline‐based adjuvant therapy has recurrence and survival rates comparable to those of primary definitive chemoradiation 10,21‐24 . Furthermore, some studies have demonstrated better QOL in patients undergoing primary surgery for OPSCC even with aRT in comparison with definitive nonsurgical protocols 22,25‐28 . Select patients who undergo definitive surgery could, therefore, benefit from further de‐intensified aRT or no adjuvant treatment.…”
Section: Introductionmentioning
confidence: 99%
“…TORS has been shown to be safe and at least as effective as traditional approaches and has reduced morbidity and quality of life in head and neck surgery . TORS has shown preservation of laryngopharyngeal function without compromising oncologic outcomes and has reduced the need for adjuvant therapy using an “inside‐out” approach . In a more recent study, TORS has also been shown to have a lower rate of positive margins when compared to non‐robotic surgery, particularly in high‐volume centers …”
Section: Resultsmentioning
confidence: 99%
“…TORS has been shown to have equivalent outcomes as CRT, and it may allow for improved long-term outcomes from CRT de-escalation. 28 Currently, there is literature to support improved quality of life in patients treated with TORS, 29,30 although the subject at the moment is controversial. Recently the ORATOR trial, a phase 2 randomized study demonstrated that patients undergoing TORS actually had worse swallowing-related quality of life scores 1 year after treatment, compared with the radiotherapy-treated group.…”
Section: Treatmentmentioning
confidence: 99%